El perjuicio a terceros de buena fe por la ejecución de negocios jurídicos simulados - Cedeño Escobar, Francisco Nicolás (2017)
The simulation has led to develop different meanings of this broad topic that in the daily life of the human being is manifested as a latent practice, the same that entails the effects that this act will produce on the intervening parties or third holders of rights over the object of the legal business. In a first space must be observed and analyzed the importance of the will and consent as marrows of the formation of the legal business, because although it is true, only legal effects will occur if there is the intervention of human will and consent for the conformation of the legal business. Then the simulation, its structure and its classes are included in order to specify the effects that it will have and how it causes damage. Finally, an analysis is obtained of the effects of the simulation on the parties of the legal business or third parties not involved in it, the importance of its legality or illegality and the approach to the nullity or inexistence of the business itself by effect of the simulation.